2007
DOI: 10.1080/03067310701455955
|View full text |Cite
|
Sign up to set email alerts
|

Determination of volatilization (dissipation) and secondary deposition of pesticides in a field study using passive dosimeters

Abstract: The volatilization and secondary deposition of the herbicides prosulfocarb and pendimethalin were measured using passive dosimeters with Chinese cabbage and soil as collective material. Passive dosimeters were placed in the field before spraying and at three distances downwind after spraying. The volatilization of prosulfocarb and pendimethalin determined as dissipation was 80 and 60% of the applied amount from the cabbage surface, while no significant loss was measured from soil surfaces after 48 h. The secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…Notably, during the push-pull experiment, evening temperatures were an average of 22 °C, around 1 °C lower than during the push-only experiment. Increases in temperature increase the effective vapour pressure of a chemical and therefore the volatilization rate [ 100 ]. Cooler temperature conditions lead to lower transfluthrin evaporation rates and it has been previously suggested that the protective efficacy of passively emanated transfluthrin from hessian fabric reduces when temperatures are < 23 °C [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, during the push-pull experiment, evening temperatures were an average of 22 °C, around 1 °C lower than during the push-only experiment. Increases in temperature increase the effective vapour pressure of a chemical and therefore the volatilization rate [ 100 ]. Cooler temperature conditions lead to lower transfluthrin evaporation rates and it has been previously suggested that the protective efficacy of passively emanated transfluthrin from hessian fabric reduces when temperatures are < 23 °C [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pollen groups from the same locations displayed consistent differences in concentrations and tPHQ values. Pesticides can reach the area outside crops by drift during and after spraying and by volatilization from soil and plant surface (Himel et al, 1990), generating pesticide-enriched rainfalls (Jensen et al, 2007), and atmospheric dust deposition (Wheatley, 1973). Spray drift is a mechanism of pesticide droplets moving through air or water (Felsot et al, 2010), and a constant concern of pesticide use (Damalas, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also highlighted the role of herbicide drift into adjacent semi-natural habitats as a major factor affecting plant composition and richness of grasslands (Aude et al 2003). Jensen et al (2007) demonstrated that low dosages of herbicides have the potential to affect plant success significantly, and in turn reduce the number of species and affect the species composition (Damgaard et al 2008). Although field monitoring can track changes in community composition following exposure to multiple drift agents (Boutin and Jobin 1998), only field experiments can distinguish between individual and cumulative effects.…”
Section: Introductionmentioning
confidence: 99%